A Rare Case of Systemic Lupus Erythematosus with Concomitant Inflammatory Bowel Disease: A Diagnostic and Therapeutic Challenge - Made Cantika Kumara Dipa; Ketut Suryana (HM Publisher, 2025)
Background: Systemic lupus erythematosus (SLE) and inflammatory bowel disease (IBD) are chronic conditions with complex pathophysiologies. While both diseases can affect the gastrointestinal tract, their co-occurrence is rare and presents unique diagnostic and therapeutic challenges. This case report describes a patient with SLE who developed IBD, highlighting the complexities of managing such cases. Case presentation: A 27-year-old female with a history of SLE presented with hematochezia, abdominal pain, and weight loss. A colonoscopy revealed findings consistent with IBD. The patient's SLE was well-controlled on immunosuppressive therapy, but the addition of IBD required careful medication adjustments to manage both conditions effectively. Conclusion: The coexistence of SLE and IBD is an uncommon but significant clinical scenario. This case underscores the importance of a thorough evaluation of IBD in SLE patients presenting with gastrointestinal symptoms. Furthermore, it emphasizes the need for a multidisciplinary approach to optimize treatment strategies and improve patient outcomes.